Effectiveness of UseWhatsapp Groups in Implementation of Classes for Mothers Toddlers Aged 0-1 Years Against Knowledge of Mothers Toddlers in the Technical Implementation Unit, Barong Tongkok Community Health Center in 2022 - Satryani, Satryani; Mardiana, Nina; Rahman, Gajali (Jurnal KESANS : Kesehatan dan Sains, 2022)
Introduction: Children are valuable assets of the nation as the successor of the nation. Efforts to realize the need for an environment that is conducive to quality growth and development from an early age. One of the government programs is the establishment of a class of toddler mothers. However, during the COVID-19 pandemic, the implementation of the toddler mother class was postponed until the conditions were free from the COVID-19 pandemic. The solution to this problem is to conduct an online toddler mother class using WhatsApp Group media. Objective: The purpose of this study is to determine the effectiveness of using Whatsapp Grub in the implementation of classes for toddlers aged 0-1 years in increasing the knowledge of toddler mothers. Method: This study used Quasi experimental design with a two-grub pretest-posttest design approach. This study compared the knowledge of toddler mothers before and after treatment. Results: The results of the study obtained a p value of 0.000 or < 0.005 which means that the use of Whatsapp Group in the class of toddler mothers is effective in increasing the knowledge of toddler mothers. Discussion: Various factors that can influence knowledge are the sources of information obtained. The class of toddler mothers both using Whatsapp media and conventionally helps mothers to increase knowledge. Conclusion: Online classes for mothers of toddlers can improve the knowledge of mothers of toddlers. From the results of this study, it can be seen that we can improve knowledge and skills even though not through face-to-face learning, especially during the COVID-19 pandemic